Análise e Controle Ótimo da COVID-19 no Brasil usando Modelo Epidemiológico SI Intervalar - Campos, J. R.; Pena, I. Da S.; Silva, G. N. [UNESP]; Lodwick, W. A. (Sociedade Brasileira de Matemática Aplicada e Computacional - SBMAC, 2024)
The objective of this paper is to provide possible scenarios for the evolution of Coronavirus Disease-19 (COVID-19) from the application of optimal control strategies. Provided that data on the novel coronavirus (SARS-CoV-2) are fraught of uncertainty or even lack of information, interval mathematical models are feasible for the study of epidemiological models related to COVID-19. Thus, the interval SI epidemiological model and the corresponding interval optimal control problem were proposed. The solution of the interval optimal control problem illustrates pessimistic and optimistic scenarios for the evolution of the pandemic in Brazil. Two decision-making criterias under uncertainty have been considered and they can assist the decision making process by public health workers. Both criterias take into account costs associated with the decision-making.

O objetivo deste trabalho é fornecer cenários possíveis da evolução da pandemia ocasionada pela COVID-19 a partir da aplicação de estratégias de controle ótimo. Uma vez que os dados sobre o coronavírus SARS-CoV-2 são repletos de incerteza ou mesmo falta de informação, a modelagem matemática intervalar é viável para o estudo de modelos epidemiológicos relacionados à COVID-19. Assim, foi proposto o modelo epidemiológico SI intervalar e o problema de controle ótimo intervalar correspondente. A solução do problema de controle ótimo intervalar ilustra cenários pessimistas e otimistas para a evolução da pandemia no Brasil. Dois critérios de tomada de decisão sob incerteza foram considerados e podem auxiliar os agentes de saúde pública. Ambos os critérios levam em consideração custos associados à tomada de decisão.
Keywords: COVID-19; interval SI epidemiological model; interval optimal control problem; constrained interval arithmetic; decision-making; COVID-19; modelo epidemiológico SI intervalar; controle ótimo intervalar; aritmética intervalar restrita; tomada de decisão